On Generalized Absolute Riesz Summability Method - Kartal, Bağdagül (Communications in Mathematics and Applications, 2017)
This paper presents a generalization of a known theorem dealing with absolute Riesz summability of infinite series to the ${φ}-|\bar{N},p_{n};δ|_{k}$ summability.
Keywords: Riesz mean; summability factor; almost increasing sequences; infinite series; Hölder inequality; Minkowski inequality.